Design and analysis of dual U slot reflectarray antenna for X-band applications - Ismail, M. Y.; Malik, H. I.; Amin, M. (IOP Publishing, 2017)
A novel design of a dual frequency single layer reflectarray antenna is presented for X-band frequency applications. Dual U slots embedded on conventional rectangular microstrip reflectarray have been designed to attain a dual frequency operation. A detailed analysis of the effect on surface current distributions with the introduction of dual U slots is presented. Moreover a parametric study on the variation of significant dimensions of the design have been carried out and analysed thoroughly using a commercially available CST computer model. Proposed design configurations were fabricated above a 0.508 mm thick substrate of Rogers Duroid 5880. The dual U slot configuration offers a significant dual frequency behavior at 8.54 and 11.56 GHz with 10% bandwidth improvement of 47 and 56 MHz with a reflection loss of -4.54 and 4.11 dB respectively.